2021
DOI: 10.3389/fmicb.2021.804949
|View full text |Cite
|
Sign up to set email alerts
|

Host Immune Responses to Clostridioides difficile: Toxins and Beyond

Abstract: Clostridioides difficile is often resistant to the actions of antibiotics to treat other bacterial infections and the resulting C. difficile infection (CDI) is among the leading causes of nosocomial infectious diarrhea worldwide. The primary virulence mechanism contributing to CDI is the production of toxins. Treatment failures and recurrence of CDI have urged the medical community to search for novel treatment options. Strains that do not produce toxins, so called non-toxigenic C. difficile, have been known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 184 publications
(265 reference statements)
1
15
0
Order By: Relevance
“…According to a previous study, proteomic analysis of C. difficile revealed that several other virulence factors such as extracellular proteases, surface layer proteins (SLP) A, cell wall-binding protein (CWP), collagen-binding protein (CbpA), fibronectin-binding protein (FBP) type IV pili and flagella can also contribute to disease severity and host colonization [80][81][82][83]. These bacterial factors possess potent pro-inflammatory activities, and are capable of causing intestinal mucosal injury by promoting inflammatory responses [80,[84][85][86]. For instance, recognition of C. difficile flagellin by toll-like receptor 5 (TLR-5) results in activation of NF-κB and MAPKs pathways, which in turn can induce the production of additional growth factors and cytokines [87].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, proteomic analysis of C. difficile revealed that several other virulence factors such as extracellular proteases, surface layer proteins (SLP) A, cell wall-binding protein (CWP), collagen-binding protein (CbpA), fibronectin-binding protein (FBP) type IV pili and flagella can also contribute to disease severity and host colonization [80][81][82][83]. These bacterial factors possess potent pro-inflammatory activities, and are capable of causing intestinal mucosal injury by promoting inflammatory responses [80,[84][85][86]. For instance, recognition of C. difficile flagellin by toll-like receptor 5 (TLR-5) results in activation of NF-κB and MAPKs pathways, which in turn can induce the production of additional growth factors and cytokines [87].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about CDT and its role in immune response; however, CDT may enhance the disruption of the host’s protective mechanisms stimulated by C. difficile toxins A and B [ 28 ]. It has been shown that CDT enhances the virulence of RT027 strains in animal models by inducing pathogenic host inflammation, resulting in eosinophil apoptosis in the colon and blood [ 29 ].…”
Section: In Vitro Effects Of Cdtmentioning
confidence: 99%
“…As there are recent and excellent reviews on the immune response to C. difficile [ 10 , 42 , 43 ], in this section, we present the main characteristics of this host-pathogen interaction.…”
Section: Essential Concepts Of the Immune Response During CDImentioning
confidence: 99%